Determinant of Stunting among Toddler in East Nusa Tenggara, Indonesia - Uly Agustine; Shelfi Dwi Retnani Putri Santoso; Grasiana Florida Boa; Sri Mugianti; Yosephina Elizabeth Sumartini Gunawan (Babali Health, 2022)
Introduction: Information on risk factors related to stunting is required as basic information in providing appropriate interventions in reducing the incidence of stunting. This study aimed to determine the relative risk factors for stunting. Methods: The sample of 75 infants was selected by proportional cluster random sampling. The study design was a descriptive correlation by analyzing primary data through observation and interviews using questionnaires and secondary data through Mother and Children Handbook (MCH) observation. Data analysis uses logistic regression. Results: Maternal education (p=0.005; OR=0.241), Maternal Occupation (p=0.005; OR=4.926), Father Occupation (p=0.000; OR=0.137), Maternal age at pregnancy (p=0.084; OR=1.775), Maternal Hemoglobin level at pregnancy (p=0.114; OR=2.917), Maternal arm circumference at pregnancy (p=0.000; OR=7.313), Ante Natal Care frequency (p=0.802; OR=0.889), Parenting (p=0.000; OR=0.323), Weight at birth (p=0.001; OR=6.424), Length of breastfeeding (p=0.005; OR=4.219), Age when starting to get complementary foods (p=0.000; OR=7.313), Dietary habit of children (p=0.090; OR=0.404), Infection history at children (p=0.001; OR=0.353). Conclusion: The risk factors for stunting are maternal education, maternal occupation, father occupation, maternal arm circumference at pregnancy, parenting, weight at birth, length of breastfeeding, age when starting to get complementary foods, and infection history in children. It is expected that stunting prevention efforts are carried out by controlling the causative factors.